STUDI KARAKTERISTIK PENENTUAN TINGKAT PEMBEBANAN KENDARAAN TERHADAP TEBAL LAPIS PERKERASAN JALAN - Sriwati, Meny (Universitas Negeri Makassar, 2014)
The purpose of this study was to determine the level of loading vehicles on thick layers of the road surface. The method used in the analysis is the method of asphalt components. The amount of load transferred through the wheels on the vehicle depending on the total weight of the vehicle axis configuration. Other vehicles with different axle load, comparable to the standard axle load by using the